SUPPLEMENTASI ROSELLA (Hibiscus sabdariffa LINN) DALAM PAKAN BUATAN TERHADAP KINERJA BENIH IKAN NILEM (Osteochilus hasselti) - mulyana mulyana1; rosmawati rosmawati (Universitas Djuanda, 2019)
The research is aimed to know the dose of Roselle in the feed that produce the best of the daily growth rate, survival rate and feed efficiency on Hard-Lipped Barb Fry. The research was using completely randomized design with 5 treatments and 3 replications. The treatments were differences in dose of Roselle in the feed (0, 10, 20, 30, and 40 g of Roselle/kg of feed). The results of the research showed that the treatment of 40 g of Roselle/kg of feed have been given significantly different effect (P <0,05) against the daily growth rate and feed efficiency, respectively 2,02% and 27,55%. Keywords: Hard-Lipped Barb, Roselle, growth.